DIFFERENCES IN CADMIUM AND LEAD ACCUMULATION BY LETTUCE (Lactuca sativa L.) DEPENDING ON THE CULTIVAR - Wojciech Tyksiński; Joanna Kurdubska (Acta Scientiarum Polonorum: Hortorum Cultus, 2005)
A differentiated ability of heavy metals accumulation was found between different lettuce cultivars. In combinations with an addition of lead and cadmium grown in autumn, the least amount of lead was accumulated by Agora, Regina and Bona cvs, while the least amount of cadmium was found in Saba and Bona cvs. In spring, Syrena cv. accumulated the least amount of lead, while Marta cv. showed the least amount of cadmium.